Upper Radical and Lower Radical - Pradjaningsih, Agustina (Majalah Ilmiah Matematika dan Statistika, 2016)
The attribute of Radical is expansion from ring character. This radical attribute could classified became two class of radical. That were upper radical and lower radical. This article will tell about two class of those radicals. Finally, from upper radical and lower radical concept could reborn the others radicals characters, which were essentially based from those two types of radicals.